Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Pasien Kanker Payudara di RSUD Raden Mattaher Jambi - Debbie Nomiko (Universitas Batanghari Jambi, 2020)
Breast cancer is a disease that occurs due to excessive growth or uncontrolled development of cells or breast tissue. Quality of life is an important goal in the treatment of cancer, and concerns about physical, psychological, body image disorders. The purpose of this study is to find out the factors related to the quality of life of breast cancer patients at Raden Mattaher Jambi Hospital in 2019. Research uses a coelative descriptive research design with a cross sectional approach. The research population is breast cancer patients who are treating at Raden Mattaher Jambi Hospital. Sampling is done on a sampling quota. Data collection instruments use the respondent's characteristic data questionnaire, coping mechanism, and quality of life questionnaire using the EORTC-QLQ 30 format. The data was analyzed univariate and bivariate with the Kai-Squared test (CI 95%). The results of the study obtained the average age of respondents was 51.8 years, the majority were elementary and high school educated with a proportion of 35.7%, and most did not work as many as 35 people (62.5%). The results of bivariate analysis that there is a relationship between the length of the cancer and the mechanism of coffee and the quality of life of breast cancer patients in Raden Mattaher Jambi Hospital. It is hoped that hospitals can facilitate the interaction activities of cancer patients through the formation of groups for cancer patients so that they can share experiences and information in terms of improving quality of life. For nursing research, it is hoped that this research can be the basic data in carrying out the next research.